Handicraft Gallery Of North Sumatera (Metaphor Architecture) (International Journal of Architecture and Urbanism, 2020)
Handicrafts are one of the cultural and tourism assets that can to encourage people’s economy and increase tourist arrivals. Local handicraft products in Indonesia have won a place in the hearts of tourists, both local and foreign tourists. Many local artisans are willing to introduce the handcrafts to the society and are also willing to develop each of their masterpieces, but, due to the lack of facility and medium support, they choose to develop their potential outside the city. Therefore, a medium that can accommodate handicrafts needed in the form of a gallery that can help the marketing of the handcrafts that will attract visitors and provides supporting facilities such as a shopping center. Handcrafts Gallery of North Sumatera is a place to centralize artisans from various regions of North Sumatera to market and introduce their featured products with direct interaction with the artisans. The research method carried out by the process of finding ideas by finding out the problems that exist in the area of the design object, then creating ideas in the design by linking each of the strengths that are also the basis in the design and with data collection methods. In addition it is carried out by the method of data collection, namely literature studies, comparative studies and field surveys. The architecture applied to this building is a metaphor architecture, which is applied to the facade and roof to create an attractive building, a building that can give its impression and image, able to trigger people's perception and imagination, and also able to display forms as attractive as possible to provide its aesthetical value to the surrounding area.